Waterproof corrosion-resistant fabric and preparation method thereof
By combining modified polyester spinning with dialdehyde-based cyclodextrin, modified permethrin microcapsules and zinc acetate, waterproof and corrosion-resistant fabrics with antibacterial, flame retardant, antistatic and deodorizing properties were prepared, and the solution was solved The fiber fabric is easy to adhere to microbial properties and lacks waterproof performance, achieving multiple performance improvements of the fabric.
Patent Information
- Application Number
- CN202411615374.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Fibrous fabrics are prone to microbial adhesion due to their porous structure and polymer chemical structure, which leads to pollution and health risks, and lacks waterproof, antistatic and flame retardant properties.
Waterproof and corrosion-resistant fabrics are prepared by reacting modified polyester spinning with dialdehyde cyclodextrin, modified permethrin microcapsules and zinc acetate. The antibacteriality of the fabric is enhanced by the combination of modified polysiloxane and quaternary ammonium salts. , flame retardant, antistatic and deodorizing properties.
The fabric is waterproof, anti-static, flame retardant and deodorizing effects, which significantly improves its corrosion resistance and safety, can effectively inhibit bacterial growth and static accumulation, and prevent combustion at high temperatures.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber fabrics, in particular to a waterproof and corrosion-resistant fabric and a preparation method thereof. Background Art
[0002] Fabric is the material used to make clothing. As one of the three elements of clothing, fabric can not only interpret the style and characteristics of clothing, but also directly influence the color and shape of clothing. The methods of making fabric include weaving, knitting and non-woven, etc. Different methods can obtain fabrics with different texture, thickness, breathability, durability and appearance.
[0003] Textile fabrics composed of fibers are conducive to the attachment of microorganisms due to their porous shape and chemical structure of high molecular polymers, making them good parasites for the survival and reproduction of microorganisms. In addition to harming the human body, the parasites will also contaminate the fibers. In order to solve the above problems, this article introduces a waterproof and corrosion-resistant fabric with antibacterial, flame retardant, antistatic and deodorizing capabilities. Summary of the invention
[0004] The purpose of the present invention is to provide a waterproof and corrosion-resistant fabric and a preparation method thereof to solve the problems existing in the prior art.
[0005] A waterproof and corrosion-resistant fabric, which is prepared by spinning modified polyester and reacting it with dialdehyde cyclodextrin, modified permethrin microcapsules and zinc acetate in sequence; The modified permethrin microcapsules are prepared by polymerizing melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde, and glutaconaldehyde and coating the permethrin emulsion to obtain permethrin microcapsules; and reacting the permethrin microcapsules with glycidyl trimethylammonium chloride and mercaptoethylamine in sequence. The modified polyester is prepared by polymerizing dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and then reacting with modified polysiloxane; The modified polysiloxane is prepared by polymerizing an organic silicon mixture.
[0006] A method for preparing a waterproof and corrosion-resistant fabric, the method for preparing the waterproof and corrosion-resistant fabric mainly comprises the following preparation steps: (1) Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 1-3:0.3-0.5:2-4:0.3-0.5, the pH was adjusted to 8.5-9 with triethanolamine, and the mixture was reacted at 70-80°C and 250-350 rpm for 20-40 min to obtain a shell prepolymer; the permethrin emulsion and the shell prepolymer were mixed in a mass ratio of 1:1 and heated at 45-55°C. , react at 250-350 rpm for 55-65 min, heat to 68-72°C, adjust pH to 4-5 with citric acid, continue to react for 55-65 min, heat to 73-77°C, adjust pH to 3-4 with citric acid, continue to react for 80-100 min, adjust pH to neutral with 20% sodium hydroxide solution, filter, and vacuum dry at -10-0°C for 20-24 h to obtain permethrin microcapsules; (2) Permethrin microcapsules, isopropanol and glycidyl trimethylammonium chloride were mixed in a mass ratio of 1:5-8:0.3-0.5, and the pH was adjusted to 6-7 with a 5-9% sodium hydroxide aqueous solution. The mixture was reacted at 70-90°C for 12-14 hours, centrifuged, separated, washed with anhydrous ethanol for 3-5 times, and dried at 70-90°C for 5-8 hours to obtain pre-modified permethrin microcapsules. Mercaptoethylamine, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:3- 5: 1.1~1.3 are mixed evenly, and under nitrogen protection, the reaction is stirred at 200~300r / min for 10~15min, and pre-modified permethrin microcapsules with a mass of 6~8 times of mercaptoethylamine are added in an ice-water bath, and the reaction is stirred at 200~300r / min for 5.5~6.5h at 45~55℃, and the extraction is performed 3~5 times with ethyl acetate solution, and the extracts are combined and vacuum dried at -10~-1℃ for 22~24h to obtain modified permethrin microcapsules; (3) The organic silicon mixture, deionized water and concentrated hydrochloric acid with a mass fraction of 36-38% are mixed in a mass ratio of 180-200:20-30:1-3, stirred at 200-300 r / min for 20-40 min, heated to 50-60°C, and continued to stir for 2-4 h. The pH was adjusted to neutral with sodium carbonate, stirred for 10-30 min, cooled to room temperature, washed with deionized water for 3-5 times, and vacuum dried at -10-0°C for 22-26 h to obtain modified polysiloxane; (4) Mix dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride in a molar ratio of 6-8:2-3:1-3:4-6:1-2:0.08-0.1, then add sodium acetate in an amount of 0.01-0.02 times the mass of dimethyl terephthalate, and heat at 210-220°C under nitrogen protection for 200-300 seconds. / min stirring reaction for 10-12h, cooling to room temperature to obtain pre-modified polyester; modifying polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water in a mass ratio of 1:5-7:0.03-0.05:4-6, stirring at 200-300r / min for 5-10min, stopping stirring, reacting at 90-100℃ for 3-4h, washing with deionized water for 3-5 times to obtain modified polyester; (5) Mix cyclodextrin, sodium periodate and deionized water in a mass ratio of 9-10:0.3-0.5:195-205, react at 18-22°C and 200-300 rpm for 45-75 min, add polyethylene glycol (0.15-0.25 times the mass of cyclodextrin), filter, and vacuum dry at -10--1°C for 22-24 h to obtain dialdehyde cyclodextrin; (6) The modified polyester is subjected to melt electrospinning, allowed to stand at 90-100°C for 6-8 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers are sequentially immersed in a dialdehyde cyclodextrin solution, a modified chlorpyrifos microcapsule solution, and a zinc acetate solution for 30-50 seconds, taken out, allowed to stand for 30-50 minutes, washed with deionized water for 3-5 times, and vacuum dried at -10--1°C for 22-24 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers are woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
[0007] As an optimization, the permethrin emulsion in step (2) is prepared by mixing styrene maleic anhydride copolymer, deionized water and ammonia water in a mass ratio of 1:2-3:0.1-0.3, stirring at 10000-14000 rpm, adding permethrin in an amount equal to the mass of styrene maleic anhydride copolymer at a uniform rate within 2-4 minutes, adjusting the pH to 5.5-6 with a 10% mass fraction anhydrous citric acid solution, and continuing stirring for 50-70 minutes.
[0008] As an optimization, the organic silicon mixture in step (3) is prepared by uniformly mixing 3-aminopropylmethyldimethoxysilane, dimethyldimethoxysilane and dimethylethoxysilane in a mass ratio of 1:4 to 6:1.
[0009] As an optimization, the melt electrospinning parameters in step (6) are: spinning temperature 260~280°C, discharge diameter 0.8~1.2mm, spinning voltage 26~30KV, and receiving distance 16~18cm.
[0010] As an optimization, the dialdehyde cyclodextrin solution in step (6) is prepared by uniformly mixing dialdehyde cyclodextrin and ethanol in a mass ratio of 1:1.
[0011] As an optimization, the modified permethrin microcapsule solution in step (6) is prepared by uniformly mixing the modified permethrin microcapsules and ethanol in a mass ratio of 1:1.
[0012] As an optimization, the zinc acetate solution in step (6) is prepared by uniformly mixing zinc acetate and ethanol in a mass ratio of 1:1.
[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the waterproof and corrosion-resistant fabric, the present invention comprises the following steps: polymerizing melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and pentanedialdehyde and coating the permethrin emulsion to obtain permethrin microcapsules; reacting the permethrin microcapsules with glycidyl trimethylammonium chloride and mercaptoethylamine in sequence to obtain modified permethrin microcapsules; polymerizing the organic silicon mixture to obtain modified polysiloxane; polymerizing dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol and (2E)-2-pentene-1,5-diol and then reacting the polymerized polysiloxane to obtain modified polyester; spinning the modified polyester and reacting the modified polyester with dialdehyde cyclodextrin, modified permethrin microcapsules and zinc acetate in sequence to obtain the waterproof and corrosion-resistant fabric.
[0014] Firstly, melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutarenedial are polymerized and coated with permethrin emulsion to obtain permethrin microcapsules; the permethrin microcapsules are reacted with glycidyltrimethylammonium chloride and mercaptoethylamine in sequence to obtain modified permethrin microcapsules. The obtained permethrin microcapsules have the effect of sustained-release mosquito repellent, and the hydroxyl groups on the microcapsules react with the epoxy groups to make the surface of the microcapsules rich in quaternary ammonium salts, which have hydrophilic groups and non-polar groups, so that it can absorb moisture in the air. This hygroscopicity helps to reduce the resistance of the material surface, thereby reducing the accumulation of static electricity, and can also form a molecular layer on the material surface, which can react with the epoxy groups. The moisture in the air combines to form conductive channels, which allow the charge to be quickly removed from the surface of the material, further enhancing its antistatic effect. The microcapsules are rich in nitrogen and decompose to produce non-flammable gases after absorbing heat. On the one hand, they can dilute the concentration of oxygen in the air and combustibles produced by the thermal decomposition of polymers. On the other hand, the nitrogen oxides produced by the decomposition capture free radicals, inhibit the chain reaction of polymers, and improve the flame retardant ability of the material. Quaternary ammonium salts can also kill bacteria by destroying cell membranes, inhibiting enzyme activity and destroying nucleic acids. These mechanisms make quaternary ammonium salts an effective bactericide, and they have a killing effect on a wide spectrum of bacteria, fungi and some viruses, thereby achieving an antibacterial effect.
[0015] Secondly, the organic silicon mixture is polymerized to obtain modified polysiloxane; dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol are polymerized and then reacted with modified polysiloxane to obtain modified polyester; the modified polyester is spun and reacted with dialdehyde cyclodextrin, modified permethrin microcapsules and zinc acetate in sequence to obtain waterproof and corrosion-resistant fabrics. The organic phosphorus in the polyester can produce phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction and thus slow down the combustion, and can generate structurally stable and non-volatile polymetaphosphoric acid during the combustion process. Polymetaphosphoric acid has a strong dehydration effect, which promotes the carbonization of the polymer into a dense and flame-retardant carbonized layer during the heating process. The carbonized layer covers the surface of the polymer, isolates the bottom material from the external oxygen, and hinders the external heat from being transferred to the base material, thereby effectively preventing the material from further pyrolysis and terminating the material. combustion, thereby improving the flame retardant ability of polyester; modified polysiloxane undergoes silylation addition with the double bonds on polyester, and polysiloxane will solidify immediately after contacting water, thereby forming a strong protective layer. In addition, polysiloxane has a large number of hydrogen bonds in its molecular structure, which can form a very tight connection between polysiloxane molecules, thereby enhancing the waterproof effect of the material, and polysiloxane has high chemical stability, which can improve the corrosion resistance of the material; cyclodextrin has deodorizing ability and can form a large number of Schiff bases through aldehyde groups combined with modified polyester fibers and modified chlorpyrifos microcapsules, which can be complexed with zinc ions. Zinc ions can interact with the negative ions of bacterial cells, causing abnormalities in enzymes and other protein mechanisms in bacterial cells, thereby destroying their biofilms and metabolic basis. In addition, zinc ions can affect bacterial DNA replication and transcription, hinder their growth and reproduction, thereby achieving the effect of inhibiting and killing bacteria. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0017] A method for preparing a waterproof and corrosion-resistant fabric mainly comprises the following preparation steps: (1) Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 1:0.3:2:0.3, the pH was adjusted to 8.5 with triethanolamine, and the mixture was reacted at 70°C and 250 rpm for 20 min to obtain a shell prepolymer; permethrin emulsion and shell prepolymer were mixed in a mass ratio of 1:1, the mixture was reacted at 45°C and 250 rpm for 55 min, the mixture was heated to 68°C, the pH was adjusted to 4 with citric acid, the reaction was continued for 55 min, the mixture was heated to 73°C, the pH was adjusted to 3 with citric acid, the reaction was continued for 80 min, the pH was adjusted to neutral with a 20% sodium hydroxide solution, the mixture was filtered, and the mixture was vacuum dried at -10°C for 20 h to obtain permethrin microcapsules; (2) Mix chlorpyrifos microcapsules, isopropanol and trimethyl ammonium chloride in a mass ratio of 1:5:0.3, adjust the pH to 6 with a 5% sodium hydroxide aqueous solution, react at 70°C for 12 hours, centrifuge, separate, wash with anhydrous ethanol three times, and dry at 70°C for 5 hours to obtain pre-modified chlorpyrifos microcapsules; mix mercaptoethylamine, tetrahydrofuran and triethylamine in a mass ratio of 1:3:1.1, stir at 200 r / min for 10 minutes under nitrogen protection, add 6 times the mass of mercaptoethylamine pre-modified chlorpyrifos microcapsules in an ice water bath, stir at 200 r / min for 5.5 hours at 45°C, extract with ethyl acetate solution three times, combine the extracts, and vacuum dry at -10°C for 22 hours to obtain modified chlorpyrifos microcapsules; (3) The organic silicon mixture, deionized water and 36% concentrated hydrochloric acid were mixed in a mass ratio of 180:20:1, stirred at 200 r / min for 20 min, heated to 50°C, and continued to stir for 2 h. The pH was adjusted to neutral with sodium carbonate, stirred for 10 min, cooled to room temperature, washed with deionized water for 3 times, and vacuum dried at -10°C for 22 h to obtain modified polysiloxane. (4) Dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 6:2:1:4:1:0.08, and then sodium acetate was added in an amount 0.01 times the mass of dimethyl terephthalate, and the mixture was stirred at 200 r / min for 10 h at 210°C under nitrogen protection, and then cooled to room temperature to obtain a pre-modified polyester; modified polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water were mixed in a mass ratio of 1:5:0.03:4, stirred at 200 r / min for 5 min, and then the stirring was stopped. The mixture was reacted at 90°C for 3 h, and then washed with deionized water for 3 times to obtain a modified polyester; (5) Cyclodextrin, sodium periodate and deionized water were mixed in a mass ratio of 9:0.3:195, reacted at 18°C and 200 rpm for 45 min, polyethylene glycol (0.15 times the mass of cyclodextrin) was added, filtered, and vacuum dried at -10°C for 22 h to obtain dialdehyde cyclodextrin; (6) The modified polyester was subjected to melt electrospinning, allowed to stand at 90°C for 6 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution, a modified chlorpyrifos microcapsule solution, and a zinc acetate solution for 30 seconds, taken out, allowed to stand for 30 minutes, washed three times with deionized water, and vacuum dried at -10°C for 22 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics. Example 2
[0018] A method for preparing a waterproof and corrosion-resistant fabric mainly comprises the following preparation steps: (1) Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 2:0.4:3:0.4, the pH was adjusted to 8.75 with triethanolamine, and the mixture was reacted at 75°C and 300 rpm for 30 min to obtain a shell prepolymer; permethrin emulsion and shell prepolymer were mixed in a mass ratio of 1:1, and the mixture was reacted at 50°C and 300 rpm for 60 min, the mixture was heated to 70°C, the pH was adjusted to 4.5 with citric acid, the reaction was continued for 60 min, the mixture was heated to 75°C, the pH was adjusted to 3.5 with citric acid, the reaction was continued for 90 min, the pH was adjusted to neutral with a 20% sodium hydroxide solution, the mixture was filtered, and the mixture was vacuum dried at -5.5°C for 22 h to obtain permethrin microcapsules; (2) Mix chlorpyrifos microcapsules, isopropanol and trimethyl ammonium chloride in a mass ratio of 1:6.5:0.4, adjust the pH to 6.5 with a 7% sodium hydroxide aqueous solution, react at 80°C for 13 hours, centrifuge, separate, wash with anhydrous ethanol 4 times, and dry at 80°C for 6.5 hours to obtain pre-modified chlorpyrifos microcapsules; mix mercaptoethylamine, tetrahydrofuran and triethylamine in a mass ratio of 1:4:1.2, stir and react at 250 r / min for 12.5 minutes under nitrogen protection, add 7 times the mass of mercaptoethylamine pre-modified chlorpyrifos microcapsules in an ice water bath, stir and react at 50°C for 6 hours at 250 r / min, extract with ethyl acetate solution 4 times, combine the extracts, and vacuum dry at -5°C for 23 hours to obtain modified chlorpyrifos microcapsules; (3) The organic silicon mixture, deionized water and 37% concentrated hydrochloric acid were mixed in a mass ratio of 190:25:2, stirred at 250 r / min for 30 min, heated to 55°C, and continued to stir for 3 h. The pH was adjusted to neutral with sodium carbonate, stirred for 20 min, cooled to room temperature, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 h to obtain modified polysiloxane. (4) Dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 7:2.5:2:5:1.5:0.09, and then 0.015 times the mass of dimethyl terephthalate sodium acetate was added, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a pre-modified polyester; modified polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water were mixed in a mass ratio of 1:6:0.04:5, stirred at 250 r / min for 7.5 minutes, and then the stirring was stopped. The mixture was reacted at 95°C for 3.5 hours, and washed with deionized water for 4 times to obtain a modified polyester; (5) Cyclodextrin, sodium periodate and deionized water were mixed in a mass ratio of 9.5:0.4:200, reacted at 20°C and 250 rpm for 60 min, polyethylene glycol (0.2 times the mass of cyclodextrin) was added, filtered, and vacuum dried at -5.5°C for 23 h to obtain dialdehyde cyclodextrin; (6) The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution, a modified chlorpyrifos microcapsule solution, and a zinc acetate solution for 40 seconds, taken out, allowed to stand for 40 minutes, washed with deionized water for 4 times, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics. Example 3
[0019] A method for preparing a waterproof and corrosion-resistant fabric mainly comprises the following preparation steps: (1) Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 3:0.5:4:0.5, the pH was adjusted to 9 with triethanolamine, and the mixture was reacted at 80°C and 350 rpm for 40 min to obtain a shell prepolymer; permethrin emulsion and shell prepolymer were mixed in a mass ratio of 1:1, and the mixture was reacted at 55°C and 350 rpm for 65 min, the mixture was heated to 72°C, the pH was adjusted to 5 with citric acid, the reaction was continued for 65 min, the mixture was heated to 77°C, the pH was adjusted to 4 with citric acid, the reaction was continued for 100 min, the pH was adjusted to neutral with a 20% sodium hydroxide solution, the mixture was filtered, and the mixture was vacuum dried at 0°C for 24 h to obtain permethrin microcapsules; (2) Mix permethrin microcapsules, isopropanol and trimethyl ammonium chloride in a mass ratio of 1:8:0.5, adjust the pH to 7 with a 9% sodium hydroxide aqueous solution, react at 90°C for 14 hours, centrifuge, separate, wash with anhydrous ethanol 5 times, and dry at 90°C for 8 hours to obtain pre-modified permethrin microcapsules; mix mercaptoethylamine, tetrahydrofuran and triethylamine in a mass ratio of 1:5:1.3, stir and react at 300 r / min for 15 minutes under nitrogen protection, add 8 times the mass of mercaptoethylamine pre-modified permethrin microcapsules in an ice water bath, stir and react at 55°C at 300 r / min for 6.5 hours, extract with ethyl acetate solution 5 times, combine the extracts, and vacuum dry at -1°C for 24 hours to obtain modified permethrin microcapsules; (3) The organic silicon mixture, deionized water and concentrated hydrochloric acid with a mass fraction of 38% were mixed in a mass ratio of 200:30:3, stirred at 300 r / min for 40 min, heated to 60°C, and continued to stir for 4 h. The pH was adjusted to neutral with sodium carbonate, stirred for 30 min, cooled to room temperature, washed with deionized water for 5 times, and vacuum dried at 0°C for 26 h to obtain modified polysiloxane; (4) Dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 8:3:3:6:2:0.1, and then sodium acetate was added in an amount of 0.02 times the mass of dimethyl terephthalate, and the mixture was stirred at 220°C, 300 r / min for 12 hours under nitrogen protection, and cooled to room temperature to obtain a pre-modified polyester; modified polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water were mixed in a mass ratio of 1:7:0.05:6, stirred at 300 r / min for 10 minutes, and the stirring was stopped. The mixture was reacted at 100°C for 4 hours, and washed with deionized water for 5 times to obtain a modified polyester; (5) Cyclodextrin, sodium periodate and deionized water were mixed in a mass ratio of 10:0.5:205, reacted at 22°C and 300 rpm for 75 min, polyethylene glycol (0.25 times the mass of cyclodextrin) was added, filtered, and vacuum dried at -1°C for 24 h to obtain dialdehyde cyclodextrin; (6) The modified polyester was subjected to melt electrospinning, allowed to stand at 100°C for 8 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution, a modified chlorpyrifos microcapsule solution, and a zinc acetate solution for 50 seconds, taken out, allowed to stand for 50 minutes, washed with deionized water for 5 times, and vacuum dried at -1°C for 24 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
[0020] Comparative Example 1 A method for preparing a waterproof and corrosion-resistant fabric mainly comprises the following preparation steps: Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 2:0.4:3:0.4, the pH was adjusted to 8.75 with triethanolamine, and the mixture was reacted at 75°C and 300rpm for 30min to obtain a shell prepolymer; permethrin emulsion and shell prepolymer were mixed in a mass ratio of 1:1, reacted at 50°C and 300rpm for 60min, heated to 70°C, adjusted the pH to 4.5 with citric acid, and continued to react for 60min, heated to 75°C, adjusted the pH to 3.5 with citric acid, and continued to react for 90min, adjusted the pH to neutral with a sodium hydroxide solution with a mass fraction of 20%, filtered, and vacuum dried at -5.5°C for 22h to obtain permethrin microcapsules; The mercaptoethylamine, tetrahydrofuran and triethylamine were mixed uniformly in a mass ratio of 1:4:1.2, and stirred at 250r / min for 12.5min under nitrogen protection, and permethrin microcapsules with a mass 7 times that of mercaptoethylamine were added in an ice-water bath, and stirred at 250r / min for 6h at 50℃, and extracted with ethyl acetate solution for 4 times, and the extracts were combined and vacuum dried at -5℃ for 23h to obtain modified permethrin microcapsules; The organic silicon mixture, deionized water and concentrated hydrochloric acid with a mass fraction of 37% were mixed in a mass ratio of 190:25:2, stirred at 250 r / min for 30 minutes, heated to 55°C, and continued to stir for 3 hours. The pH was adjusted to neutral with sodium carbonate, stirred for 20 minutes, cooled to room temperature, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 hours to obtain modified polysiloxane. Dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 7:2.5:2:5:1.5:0.09, and then sodium acetate was added in an amount of 0.015 times the mass of dimethyl terephthalate, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a pre-modified polyester; modified polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water were mixed in a mass ratio of 1:6:0.04:5, and stirred at 250 r / min for 7.5 minutes, and then the stirring was stopped, and the mixture was reacted at 95°C for 3.5 hours, and then washed with deionized water for 4 times to obtain a modified polyester; Cyclodextrin, sodium periodate and deionized water were mixed in a mass ratio of 9.5:0.4:200, reacted at 20°C and 250rpm for 60min, polyethylene glycol (0.2 times the mass of cyclodextrin) was added, filtered, and vacuum dried at -5.5°C for 23h to obtain dialdehyde cyclodextrin; The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution, a modified permethrin microcapsule solution, and a zinc acetate solution for 40 seconds, taken out, allowed to stand for 40 minutes, washed four times with deionized water, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
[0021] Comparative Example 2 A method for preparing a waterproof and corrosion-resistant fabric mainly comprises the following preparation steps: The organic silicon mixture, deionized water and concentrated hydrochloric acid with a mass fraction of 37% were mixed in a mass ratio of 190:25:2, stirred at 250 r / min for 30 minutes, heated to 55°C, and continued to stir for 3 hours. The pH was adjusted to neutral with sodium carbonate, stirred for 20 minutes, cooled to room temperature, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 hours to obtain modified polysiloxane. Dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 7:2.5:2:5:1.5:0.09, and then sodium acetate was added in an amount of 0.015 times the mass of dimethyl terephthalate, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a pre-modified polyester; modified polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water were mixed in a mass ratio of 1:6:0.04:5, and stirred at 250 r / min for 7.5 minutes, and then the stirring was stopped, and the mixture was reacted at 95°C for 3.5 hours, and then washed with deionized water for 4 times to obtain a modified polyester; Cyclodextrin, sodium periodate and deionized water were mixed in a mass ratio of 9.5:0.4:200, reacted at 20°C and 250rpm for 60min, polyethylene glycol (0.2 times the mass of cyclodextrin) was added, filtered, and vacuum dried at -5.5°C for 23h to obtain dialdehyde cyclodextrin; The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution, a modified permethrin microcapsule solution, and a zinc acetate solution for 40 seconds, taken out, allowed to stand for 40 minutes, washed four times with deionized water, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
[0022] Comparative Example 3 A method for preparing a waterproof and corrosion-resistant fabric mainly comprises the following preparation steps: Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 2:0.4:3:0.4, the pH was adjusted to 8.75 with triethanolamine, and the mixture was reacted at 75°C and 300rpm for 30min to obtain a shell prepolymer; permethrin emulsion and shell prepolymer were mixed in a mass ratio of 1:1, reacted at 50°C and 300rpm for 60min, heated to 70°C, adjusted the pH to 4.5 with citric acid, and continued to react for 60min, heated to 75°C, adjusted the pH to 3.5 with citric acid, and continued to react for 90min, adjusted the pH to neutral with a sodium hydroxide solution with a mass fraction of 20%, filtered, and vacuum dried at -5.5°C for 22h to obtain permethrin microcapsules; The permethrin microcapsules, isopropanol and glycidyl trimethylammonium chloride were mixed in a mass ratio of 1:6.5:0.4, the pH was adjusted to 6.5 with a 7% sodium hydroxide aqueous solution, the mixture was reacted at 80°C for 13 hours, centrifuged, separated, washed with anhydrous ethanol 4 times, and dried at 80°C for 6.5 hours to obtain pre-modified permethrin microcapsules; mercaptoethylamine, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:4:1.2, stirred at 250 r / min for 12.5 minutes under nitrogen protection, pre-modified permethrin microcapsules with 7 times the mass of mercaptoethylamine were added in an ice-water bath, the mixture was stirred at 250 r / min for 6 hours at 50°C, extracted 4 times with ethyl acetate solution, the extracts were combined, and vacuum dried at -5°C for 23 hours to obtain modified permethrin microcapsules; The organic silicon mixture, deionized water and concentrated hydrochloric acid with a mass fraction of 37% were mixed in a mass ratio of 190:25:2, stirred at 250 r / min for 30 minutes, heated to 55°C, and continued to stir for 3 hours. The pH was adjusted to neutral with sodium carbonate, stirred for 20 minutes, cooled to room temperature, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 hours to obtain modified polysiloxane. Dimethyl terephthalate, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 9:7:1.5:0.09, and then sodium acetate was added in an amount of 0.015 times the mass of dimethyl terephthalate, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a pre-modified polyester; modified polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water were mixed in a mass ratio of 1:6:0.04:5, and stirred at 250 r / min for 7.5 minutes, and then the stirring was stopped, and the mixture was reacted at 95°C for 3.5 hours, and then washed with deionized water for 4 times to obtain a modified polyester; Cyclodextrin, sodium periodate and deionized water were mixed in a mass ratio of 9.5:0.4:200, reacted at 20°C and 250rpm for 60min, polyethylene glycol (0.2 times the mass of cyclodextrin) was added, filtered, and vacuum dried at -5.5°C for 23h to obtain dialdehyde cyclodextrin; The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution, a modified permethrin microcapsule solution, and a zinc acetate solution for 40 seconds, taken out, allowed to stand for 40 minutes, washed four times with deionized water, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
[0023] Comparative Example 4 Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 2:0.4:3:0.4, the pH was adjusted to 8.75 with triethanolamine, and the mixture was reacted at 75°C and 300rpm for 30min to obtain a shell prepolymer; permethrin emulsion and shell prepolymer were mixed in a mass ratio of 1:1, reacted at 50°C and 300rpm for 60min, heated to 70°C, adjusted the pH to 4.5 with citric acid, and continued to react for 60min, heated to 75°C, adjusted the pH to 3.5 with citric acid, and continued to react for 90min, adjusted the pH to neutral with a sodium hydroxide solution with a mass fraction of 20%, filtered, and vacuum dried at -5.5°C for 22h to obtain permethrin microcapsules; The permethrin microcapsules, isopropanol and glycidyl trimethylammonium chloride were mixed in a mass ratio of 1:6.5:0.4, the pH was adjusted to 6.5 with a 7% sodium hydroxide aqueous solution, the mixture was reacted at 80°C for 13 hours, centrifuged, separated, washed with anhydrous ethanol 4 times, and dried at 80°C for 6.5 hours to obtain pre-modified permethrin microcapsules; mercaptoethylamine, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:4:1.2, stirred at 250 r / min for 12.5 minutes under nitrogen protection, pre-modified permethrin microcapsules with 7 times the mass of mercaptoethylamine were added in an ice-water bath, the mixture was stirred at 250 r / min for 6 hours at 50°C, extracted 4 times with ethyl acetate solution, the extracts were combined, and vacuum dried at -5°C for 23 hours to obtain modified permethrin microcapsules; Dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 7:2.5:2:5:1.5:0.09, and then sodium acetate was added in an amount of 0.015 times the mass of dimethyl terephthalate, and the mixture was stirred at 215°C and 250 r / min under nitrogen protection for 11 hours, and then cooled to room temperature to obtain a pre-modified polyester; Cyclodextrin, sodium periodate and deionized water were mixed in a mass ratio of 9.5:0.4:200, reacted at 20°C and 250rpm for 60min, polyethylene glycol (0.2 times the mass of cyclodextrin) was added, filtered, and vacuum dried at -5.5°C for 23h to obtain dialdehyde cyclodextrin; The pre-modified polyester was melt electrospun, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution, a modified permethrin microcapsule solution, and a zinc acetate solution for 40 seconds, taken out, allowed to stand for 40 minutes, washed four times with deionized water, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
[0024] Comparative Example 5 Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 2:0.4:3:0.4, the pH was adjusted to 8.75 with triethanolamine, and the mixture was reacted at 75°C and 300rpm for 30min to obtain a shell prepolymer; permethrin emulsion and shell prepolymer were mixed in a mass ratio of 1:1, reacted at 50°C and 300rpm for 60min, heated to 70°C, adjusted the pH to 4.5 with citric acid, and continued to react for 60min, heated to 75°C, adjusted the pH to 3.5 with citric acid, and continued to react for 90min, adjusted the pH to neutral with a sodium hydroxide solution with a mass fraction of 20%, filtered, and vacuum dried at -5.5°C for 22h to obtain permethrin microcapsules; The permethrin microcapsules, isopropanol and glycidyl trimethylammonium chloride were mixed in a mass ratio of 1:6.5:0.4, the pH was adjusted to 6.5 with a 7% sodium hydroxide aqueous solution, the mixture was reacted at 80°C for 13 hours, centrifuged, separated, washed with anhydrous ethanol 4 times, and dried at 80°C for 6.5 hours to obtain pre-modified permethrin microcapsules; mercaptoethylamine, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:4:1.2, stirred at 250 r / min for 12.5 minutes under nitrogen protection, pre-modified permethrin microcapsules with 7 times the mass of mercaptoethylamine were added in an ice-water bath, the mixture was stirred at 250 r / min for 6 hours at 50°C, extracted 4 times with ethyl acetate solution, the extracts were combined, and vacuum dried at -5°C for 23 hours to obtain modified permethrin microcapsules; The organic silicon mixture, deionized water and concentrated hydrochloric acid with a mass fraction of 37% were mixed in a mass ratio of 190:25:2, stirred at 250 r / min for 30 minutes, heated to 55°C, and continued to stir for 3 hours. The pH was adjusted to neutral with sodium carbonate, stirred for 20 minutes, cooled to room temperature, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 hours to obtain modified polysiloxane. Dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 7:2.5:2:5:1.5:0.09, and then sodium acetate was added in an amount of 0.015 times the mass of dimethyl terephthalate, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a pre-modified polyester; modified polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water were mixed in a mass ratio of 1:6:0.04:5, and stirred at 250 r / min for 7.5 minutes, and then the stirring was stopped, and the mixture was reacted at 95°C for 3.5 hours, and then washed with deionized water for 4 times to obtain a modified polyester; The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution, a modified permethrin microcapsule solution, and a zinc acetate solution for 40 seconds, taken out, allowed to stand for 40 minutes, washed four times with deionized water, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
[0025] Comparative Example 6 Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 2:0.4:3:0.4, the pH was adjusted to 8.75 with triethanolamine, and the mixture was reacted at 75°C and 300rpm for 30min to obtain a shell prepolymer; permethrin emulsion and shell prepolymer were mixed in a mass ratio of 1:1, reacted at 50°C and 300rpm for 60min, heated to 70°C, adjusted the pH to 4.5 with citric acid, and continued to react for 60min, heated to 75°C, adjusted the pH to 3.5 with citric acid, and continued to react for 90min, adjusted the pH to neutral with a sodium hydroxide solution with a mass fraction of 20%, filtered, and vacuum dried at -5.5°C for 22h to obtain permethrin microcapsules; The permethrin microcapsules, isopropanol and glycidyl trimethylammonium chloride were mixed in a mass ratio of 1:6.5:0.4, the pH was adjusted to 6.5 with a 7% sodium hydroxide aqueous solution, the mixture was reacted at 80°C for 13 hours, centrifuged, separated, washed with anhydrous ethanol 4 times, and dried at 80°C for 6.5 hours to obtain pre-modified permethrin microcapsules; mercaptoethylamine, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:4:1.2, stirred at 250 r / min for 12.5 minutes under nitrogen protection, pre-modified permethrin microcapsules with 7 times the mass of mercaptoethylamine were added in an ice-water bath, the mixture was stirred at 250 r / min for 6 hours at 50°C, extracted 4 times with ethyl acetate solution, the extracts were combined, and vacuum dried at -5°C for 23 hours to obtain modified permethrin microcapsules; The organic silicon mixture, deionized water and concentrated hydrochloric acid with a mass fraction of 37% were mixed in a mass ratio of 190:25:2, stirred at 250 r / min for 30 minutes, heated to 55°C, and continued to stir for 3 hours. The pH was adjusted to neutral with sodium carbonate, stirred for 20 minutes, cooled to room temperature, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 hours to obtain modified polysiloxane. Dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride were mixed uniformly in a molar ratio of 7:2.5:2:5:1.5:0.09, and then sodium acetate was added in an amount of 0.015 times the mass of dimethyl terephthalate, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a pre-modified polyester; modified polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water were mixed in a mass ratio of 1:6:0.04:5, and stirred at 250 r / min for 7.5 minutes, and then the stirring was stopped, and the mixture was reacted at 95°C for 3.5 hours, and then washed with deionized water for 4 times to obtain a modified polyester; Cyclodextrin, sodium periodate and deionized water were mixed in a mass ratio of 9.5:0.4:200, reacted at 20°C and 250rpm for 60min, polyethylene glycol (0.2 times the mass of cyclodextrin) was added, filtered, and vacuum dried at -5.5°C for 23h to obtain dialdehyde cyclodextrin; The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers were sequentially immersed in a dialdehyde cyclodextrin solution and a modified permethrin microcapsule solution for 40 seconds, taken out, allowed to stand for 40 minutes, washed with deionized water 4 times, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers were woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
[0026] Test Example 1 Flame retardancy test The limiting oxygen index was tested according to GBT / 2406 test standard. The results are shown in Table 1.
[0027] Table 1
[0028] From the comparison of the experimental data in Table 1, it can be found that the waterproof and corrosion-resistant fabric prepared by the present invention has good flame retardancy.
[0029] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 2, which shows that the permethrin microcapsules can decompose and produce non-combustible gas after absorbing heat, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of polymers on the one hand, and the nitrogen oxides produced by decomposition can capture free radicals on the other hand, inhibit the chain reaction of polymers, improve the flame retardancy of materials, and increase the limiting oxygen index of materials; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 3, which shows that the organic phosphorus can produce phosphorus-containing free radicals, can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction to slow down the combustion, and can generate polymetaphosphoric acid with stable structure and non-volatile in the combustion process. Polymetaphosphoric acid has a strong dehydration effect, which promotes the carbonization of the polymer into a dense and flame-retardant carbonized layer during the heating process. The carbonized layer covers the surface of the polymer, isolates the bottom material from the contact with the external oxygen, and hinders the external heat from being transferred to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, improving the flame retardancy of the material, and increasing the limiting oxygen index of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 4, which indicates that when the silicon-oxygen chain burns, the silicon-oxygen bonds in the molecules will be converted into silicon-carbon bonds, forming a composite carbon layer together with the generated carbonized products. This composite carbon layer has the advantages of blocking heat, isolating oxygen, and preventing molten droplets, and seals the polymer material to prevent the combustible gas from diffusing outward, thereby improving the flame retardant ability of the material and increasing the limiting oxygen index of the material.
[0030] Test Example 2 Antimicrobial testing The test was carried out according to the GB / T20944 oscillation method, wherein the selected bacteria species were Staphylococcus aureus and Escherichia coli. The results are shown in Table 2.
[0031] Table 2
[0032] From the comparison of the experimental data in Table 2, it can be found that the waterproof and corrosion-resistant fabric prepared by the present invention has good antibacterial ability.
[0033] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 2, it can be found that the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 1, which shows that quaternary ammonium salts can kill bacteria by destroying cell membranes, inhibiting enzyme activity, and destroying nucleic acids. These mechanisms make quaternary ammonium salts an effective bactericide and have a killing effect on a wide spectrum of bacteria, fungi, and some viruses, thereby achieving an antibacterial effect; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 6, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 6, which shows that the Schiff base zinc complex can release zinc ions. Zinc ions can interact with the negative ions of bacterial cells to cause abnormalities in enzymes and other protein mechanisms in bacterial cells, thereby destroying their biofilms and metabolic basis. In addition, zinc ions can affect bacterial DNA replication and transcription, hinder their growth and reproduction, and achieve the effect of inhibiting and killing bacteria.
[0034] Test Example 3 Antistatic test The surface resistivity of the samples was measured using a surface resistance tester. The results are shown in Table 3.
[0035] Table 3
[0036] From the comparison of the experimental data in Table 3, it can be found that the waterproof and corrosion-resistant fabric prepared by the present invention has good antistatic ability.
[0037] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 3, it can be found that the surface resistivity of Examples 1, 2, 3 is greater than that of Comparative Example 1, which shows that the quaternary ammonium salt has a hydrophilic group and a non-polar group, which enables it to absorb moisture in the air. This hygroscopicity helps to reduce the resistance of the material surface, thereby reducing the accumulation of static electricity, and can also form a molecular layer on the material surface. This layer of molecules can combine with moisture in the air to form conductive channels. These conductive channels allow charges to be quickly removed from the material surface, further enhancing its antistatic effect.
[0038] Test Example 4 Deodorization test The ammonia removal rate was tested according to the CB / T33610.2 test tube method. The results are shown in Table 4.
[0039] Table 4
[0040] From the comparison of the experimental data in Table 4, it can be found that the waterproof and corrosion-resistant fabric prepared by the present invention has good deodorizing ability.
[0041] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5 in Table 4, it can be found that the ammonia removal rates of Examples 1, 2, 3 are greater than those of Comparative Example 5, which indicates that cyclodextrin has the ability to deodorize.
[0042] Test Example 5 Waterproof and corrosion resistance test Waterproof test: Use a contact angle meter to test the water contact angle; Corrosion resistance test: The fiber was immersed in artificial sweat at 37°C for 3 days, and the mass retention rate was tested, where mass retention rate = mass before immersion / mass after immersion * 100%. The results are shown in Table 4.
[0043] Table 5
[0044] From the comparison of the experimental data in Table 5, it can be found that the high-strength corrosion-resistant fiber prepared in the present invention has good waterproof and corrosion-resistant capabilities.
[0045] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 5, it can be found that Examples 1, 2, 3 have a larger mass retention rate and a larger water contact angle than Comparative Example 4, which indicates that polysiloxane solidifies immediately after contacting water to form a strong protective layer. In addition, polysiloxane has a large number of hydrogen bonds in its molecular structure, which can form a very tight connection between polysiloxane molecules, thereby enhancing the waterproof effect of the material. Polysiloxane has high chemical stability and can improve the corrosion resistance of the material.
[0046] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A waterproof and corrosion-resistant fabric, characterized in that: The waterproof and corrosion-resistant fabric is prepared by spinning modified polyester and reacting it with dialdehyde cyclodextrin, modified permethrin microcapsules and zinc acetate in sequence; The modified permethrin microcapsules are prepared by polymerizing melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde, and glutaconaldehyde and coating the permethrin emulsion to obtain permethrin microcapsules; and reacting the permethrin microcapsules with glycidyl trimethylammonium chloride and mercaptoethylamine in sequence. The modified polyester is prepared by polymerizing dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and then reacting with modified polysiloxane; The modified polysiloxane is prepared by polymerizing an organic silicon mixture.
2. A method for preparing a waterproof and corrosion-resistant fabric, characterized in that: The preparation method of the waterproof and corrosion-resistant fabric mainly includes the following preparation steps: (1) Melamine, 4,6-diamino-2-hydroxy-1,3,5-triazine, glutaraldehyde and glutaraldehyde were mixed in a molar ratio of 1-3:0.3-0.5:2-4:0.3-0.5, the pH was adjusted to 8.5-9 with triethanolamine, and the mixture was reacted at 70-80°C and 250-350 rpm for 20-40 min to obtain a shell prepolymer; the permethrin emulsion and the shell prepolymer were mixed in a mass ratio of 1:1 and heated at 45-55°C. , react at 250-350 rpm for 55-65 min, heat to 68-72°C, adjust pH to 4-5 with citric acid, continue to react for 55-65 min, heat to 73-77°C, adjust pH to 3-4 with citric acid, continue to react for 80-100 min, adjust pH to neutral with 20% sodium hydroxide solution, filter, and vacuum dry at -10-0°C for 20-24 h to obtain permethrin microcapsules; (2) Permethrin microcapsules, isopropanol and glycidyl trimethylammonium chloride were mixed in a mass ratio of 1:5-8:0.3-0.5, and the pH was adjusted to 6-7 with a 5-9% sodium hydroxide aqueous solution. The mixture was reacted at 70-90°C for 12-14 hours, centrifuged, separated, washed with anhydrous ethanol for 3-5 times, and dried at 70-90°C for 5-8 hours to obtain pre-modified permethrin microcapsules. Mercaptoethylamine, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:3- 5: 1.1~1.3 are mixed evenly, and under nitrogen protection, the reaction is stirred at 200~300r / min for 10~15min, and pre-modified permethrin microcapsules with a mass of 6~8 times of mercaptoethylamine are added in an ice-water bath, and the reaction is stirred at 200~300r / min for 5.5~6.5h at 45~55℃, and the extraction is performed 3~5 times with ethyl acetate solution, and the extracts are combined and vacuum dried at -10~-1℃ for 22~24h to obtain modified permethrin microcapsules; (3) The organic silicon mixture, deionized water and concentrated hydrochloric acid with a mass fraction of 36-38% are mixed in a mass ratio of 180-200:20-30:1-3, stirred at 200-300 r / min for 20-40 min, heated to 50-60°C, and continued to stir for 2-4 h. The pH was adjusted to neutral with sodium carbonate, stirred for 10-30 min, cooled to room temperature, washed with deionized water for 3-5 times, and vacuum dried at -10-0°C for 22-26 h to obtain modified polysiloxane; (4) Mix dimethyl terephthalate, 1,5-pentanediamine, methyl dichlorophosphine, pentanediol, (2E)-2-pentene-1,5-diol and aluminum chloride in a molar ratio of 6-8:2-3:1-3:4-6:1-2:0.08-0.1, then add sodium acetate in an amount of 0.01-0.02 times the mass of dimethyl terephthalate, and heat at 210-220°C under nitrogen protection for 200-300 seconds. / min stirring reaction for 10-12h, cooling to room temperature to obtain pre-modified polyester; modifying polysiloxane, pre-modified polyester, chloroplatinic acid and deionized water in a mass ratio of 1:5-7:0.03-0.05:4-6, stirring at 200-300r / min for 5-10min, stopping stirring, reacting at 90-100℃ for 3-4h, washing with deionized water for 3-5 times to obtain modified polyester; (5) Mix cyclodextrin, sodium periodate and deionized water in a mass ratio of 9-10:0.3-0.5:195-205, react at 18-22°C and 200-300 rpm for 45-75 min, add polyethylene glycol (0.15-0.25 times the mass of cyclodextrin), filter, and vacuum dry at -10--1°C for 22-24 h to obtain dialdehyde cyclodextrin; (6) The modified polyester is subjected to melt electrospinning, allowed to stand at 90-100°C for 6-8 hours, and naturally cooled to room temperature to obtain polyester fibers; the polyester fibers are sequentially immersed in a dialdehyde cyclodextrin solution, a modified chlorpyrifos microcapsule solution, and a zinc acetate solution for 30-50 seconds, taken out, allowed to stand for 30-50 minutes, washed with deionized water for 3-5 times, and vacuum dried at -10--1°C for 22-24 hours to obtain waterproof and corrosion-resistant fibers; the waterproof and corrosion-resistant fibers are woven into fabrics to obtain waterproof and corrosion-resistant fabrics.
3. The method for preparing a waterproof and corrosion-resistant fabric according to claim 2, characterized in that: The permethrin emulsion in step (2) is prepared by mixing styrene maleic anhydride copolymer, deionized water and ammonia water in a mass ratio of 1:2-3:0.1-0.3, stirring at 10000-14000 rpm, adding permethrin in an amount equal to the mass of styrene maleic anhydride copolymer at a uniform rate within 2-4 minutes, adjusting the pH to 5.5-6 with a 10% mass fraction anhydrous citric acid solution, and continuing stirring for 50-70 minutes.
4. The method for preparing a waterproof and corrosion-resistant fabric according to claim 2, characterized in that: The organic silicon mixture in step (3) is prepared by uniformly mixing 3-aminopropylmethyldimethoxysilane, dimethyldimethoxysilane and dimethylethoxysilane in a mass ratio of 1:4 to 6:
1.
5. The method for preparing a waterproof and corrosion-resistant fabric according to claim 2, characterized in that: The melt electrospinning parameters of step (6) are: spinning temperature 260-280°C, discharge diameter 0.8-1.2 mm, spinning voltage 26-30 KV, and receiving distance 16-18 cm.
6. The method for preparing a waterproof and corrosion-resistant fabric according to claim 2, characterized in that: The dialdehyde cyclodextrin solution in step (6) is prepared by uniformly mixing dialdehyde cyclodextrin and ethanol in a mass ratio of 1:
1.
7. The method for preparing a waterproof and corrosion-resistant fabric according to claim 2, characterized in that: The modified permethrin microcapsule solution in step (6) is prepared by uniformly mixing the modified permethrin microcapsules with ethanol in a mass ratio of 1:
1.
8. The method for preparing a waterproof and corrosion-resistant fabric according to claim 2, characterized in that: The zinc acetate solution in step (6) is prepared by uniformly mixing zinc acetate and ethanol in a mass ratio of 1:1.
Citation Information
Patent Citations
Polyester fibre surface coating material for sea mooring rope and production process of polyester fibre surface coating material
CN102465447A
Method for fixing cyclodextrins on fabric through resin crosslinking initiated by ultraviolet
CN102517911A
Anti-mosquito fabric processing method
CN107904959A
Processing technique of flame-retardant antibacterial polyester fabric
CN110804864A
High-performance Anti-fungal, Anti-bacterial, insecticidal and deodorizing microcapsule, and application thereof
US20170079280A1
